Genome-wide transcriptome analysis reveal the molecular mechanism for triggering the formation of purple leaves in rice mutants nip-lpl and nip-dpl - Wang, Chengyu; Zhao, Hongyu; Zhou, Yujie; Zhang, Haipeng; Chen, Xinyu; Liang, Weifang; Zheng, Han; Hou, Fan; Zhang, Junjie; Xie, Liujie; Zhao, Mingwei; Zheng, Bingsong; et al. (Frontiers in Plant Science, 2025)
IntroductionThe color of rice leaves are important agronomic traits that directly influence the proportion of sunlight energy utilization and ultimately affect the yield and quality, so it is crucial to excavate the mechanism of regulating rice leave color. MethodsTo investigate the molecular mechanism that triggers the purple color in rice leaf, phenotypic characterization and genome-wide transcriptome analysis were conducted using the japonica rice cultivar nipponbare (Nip) and its two purple leaf mutants, nip-light purple leaf (nip-lpl) and nip-deep purple leaf (nip-dpl), are rice purple leaf mutants from Nip’s EMS mutant library.ResultsA total of 2247, 5484, 4525, 2103, 4375 and7029DEGs (differentially expressed genes) were identified in nip-a vs nip-lpl-a, nip-a vs nip-dpl-a, nip-c vs nip-dpl-c, nip-c vs nip-lpl-c, nip-lpl-c vs nip-dpl-c, nip-lpl-a vs nip-dpl-a, respectively. KEGG (Kyoto Encyclopedia of Genes and Genomes) analysis showed that the DEGs were significantly enriched in phenylalanine biosynthesis, terpenoid backbone biosynthesis, secondary metabolite biosynthesis, and hormones. Additionally, WGCNA (Weighted Gene Co-expression Network Analysis) showed that the darkmagenta module was associated with the purple color mainly due to the accumulation of anthocyanin in the leaves of the mutant rice. This module revealed three pathways for anthocyanin synthesis: phenylalanine could be catalyzed by phenylalanine lyase and cinnamic acid hydroxylase, etc., to generate dihydroxyflavone and ultimately anthocyanin. Furthermore, we speculated that the elevated expression of three hub genes (PAL, CHI and CHS) in nip-lpl/dpl leads to increased anthocyanin content relative to Nip.DiscussionThese results not only revealed the molecular mechanism triggering leaf purple color in the rice mutants nip-lpl/dpl but also contributed greatly to identified potential genetic engineering targets for breeding anthocyanin-rich rice.